1985
DOI: 10.1007/bf00544371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rifampicin treatment on hepatic drug metabolism and serum bile acids in patients with primary biliary cirrhosis

Abstract: Six patients with primary biliary cirrhosis (PBC) were treated with a daily oral dose of 600 mg rifampicin for 2 weeks to induce the hepatic metabolism of drugs and bile acids. On rifampicin 5 of 6 patients experienced a pronounced decrease of their pruritus. In all patients the oxidative cytochrome P-450 dependent drug metabolism was induced as shown by an increase of antipyrine-clearance from 36.3 +/- 8.8 to 80.6 +/- 20.1 ml/min and an enhanced urinary excretion of 6-beta-hydroxycortisol from 454 +/- 1.99 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 9 publications
1
21
0
1
Order By: Relevance
“…Although this commonly used antibiotic does not at all induce P-450p in the rat (23) it is an effective inducer of the orthologous liver enzyme, LM3c (23), in the rabbit. Treatment of patients with rifampicin increases production of 6 f-hydroxysteroids in the urine (38). Because HLp appears to be the major steroid 6 ,B-hydroxylase in human liver (39) induction of HLp by rifampicin would provide an explanation for these earlier observations and the breath test results presented here.…”
Section: Discussionsupporting
confidence: 51%
“…Although this commonly used antibiotic does not at all induce P-450p in the rat (23) it is an effective inducer of the orthologous liver enzyme, LM3c (23), in the rabbit. Treatment of patients with rifampicin increases production of 6 f-hydroxysteroids in the urine (38). Because HLp appears to be the major steroid 6 ,B-hydroxylase in human liver (39) induction of HLp by rifampicin would provide an explanation for these earlier observations and the breath test results presented here.…”
Section: Discussionsupporting
confidence: 51%
“…Bilirubin undergoes glucuronidation prior to excretion in the bile. There are data suggesting that RIM might enhance the hepatic clearance of bilirubin (36)(37)(38). However, in a study conducted in subjects given RIM for 30 days, bilirubin GT activity was reported to be insensitive to the treatment (39).…”
Section: Inducton Properties Of Rifampicin and Rifabutin In Animalsmentioning
confidence: 99%
“…Significant decreases of transaminases [10,12], gamma-glutamyltransferase [10,12,13], alkaline phosphatase [10] and total bile salt levels [8,10,12] were observed. Bilirubin was not significantly affected in the study populations mentioned [7][8][9][10][11][12][13], but there was a trend towards lower levels in one long-term study [12]. However, at least two patients from other studies are likely to have shown clear reductions of bilirubin during treatment with rifampicin: There was a decline observed from 9.0 to 2.9 mg/dl in [7], and from 16.80 to 10.50 mg/dl in [8].…”
mentioning
confidence: 96%
“…Before the common use of UDCA in cholestatic liver disease was established [6], small trials with rifampicin in cholestatic liver disease had shown marked improvement of pruritus [7][8][9][10][11][12][13]. In PBC, three trials administered rifampicin for 2 weeks [8][9][10].…”
mentioning
confidence: 98%
See 1 more Smart Citation